THE DEVELOPMENT OF AN ILLUSTRATED CHILDREN’S STORYBOOK - Fatmawati, Diana; Ulfah Hoesny, Mariana; Yuni Lestari, Pritantina (ENGLISH, 2024)
Illustrated children's storybook is an effective medium used to introduce various things to children. Through this book we can provide new understanding and knowledge in a fun way. The presentation in the form of a story and pictures can be more easily understood and remembered by children. Therefore, they can more easily receive and understand information effectively and efficiently. Because of that, many teachers and parents introduce storybooks to their children. This study used design and development research methods. This design was chosen because it is most suitable for creating a new product. The product developed is a children's storybook that introduces culture in tourism places. The objectives of this research are (1) to introduce the culture of tourist attractions to children through picture storybooks; (2) to provide a solution to the problem of lack of socialization about culture in tourism places. The final result of this research is an illustrated storybook for children. The book consists of 50 pages with 25 illustrations. The story presented contains cultural information from six tourism spots. The proportion of stories in this book includes 70% illustration and 30% narration. This research is useful for cultural tourism places in Malang and D4 English Language Tourism Industry students.